2009
DOI: 10.1128/aem.02576-08
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Oligonucleotide Primer Extension as a Time- and Cost-Effective Approach for Quantitative Determination of Bifidobacterium spp. in Infant Feces

Abstract: The Bifidobacterium spp. present in 10 infant fecal samples (4 from infants with eczema and 6 from healthy infants) were quantified with both hierarchical oligonucleotide primer extension (HOPE) and fluorescence in situ hybridization-flow cytometry. The relative abundances of Bifidobacterium longum and B. catenulatum with respect to the total bifidobacteria had a poor correlation (, <0.600; P value, >0.208), presumably due to differences in primer specificity and the level of hybridization stringency of both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This method allows for the simultaneous monitoring of relative abundances of AOB, NOB and comammox groups, which can be used to provide indicative data of nitrification performance and efficiency. Coupled with previous application of HOPE to a variety of target bacteria and sample types [711], this study demonstrates the versatility and applicability of HOPE for a wide range of microbial ecology studies.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…This method allows for the simultaneous monitoring of relative abundances of AOB, NOB and comammox groups, which can be used to provide indicative data of nitrification performance and efficiency. Coupled with previous application of HOPE to a variety of target bacteria and sample types [711], this study demonstrates the versatility and applicability of HOPE for a wide range of microbial ecology studies.…”
Section: Resultssupporting
confidence: 58%
“…The HOPE method had been previously validated against other conventional methods such as qPCR and FISH [7, 8, 11]. In this study, to validate the data obtained from HOPE, the relative abundances of nitrifying bacterial populations in the trickling biofilter and in samples collected from a full-scale WWTP were further validated against results from amplicon sequencing (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 27 vaginal-delivered babies (14 non-eczema controls and 13 eczema infants) were sampled for their feces at 1, 3 and 12 months of age. To evaluate if Bifidobacterium , Enterococcus and Enterobacteriaceae (including Klebsiella and Shigella ) could serve as potential biomarkers that are present in different abundances among eczema and non-eczema infants, their relative abundances in the collected feces were quantified using a rapid molecular tool (HOPE, hierarchical oligonucleotide primer extension) developed for microbial source tracking and community analysis [24] , [25] . The results showed that at the time points sampled, the relative abundances of Bifidobacterium spp.…”
Section: Resultsmentioning
confidence: 99%
“…The approach has been applied to the qualitative and quantitative analyses of functionally important indicators such as Bacteroides, Parabacteroides and Bifidobacterium spp. in faeces and domestic wastewater, and successfully discriminated faecal contamination of human, swine and bovine origins (9)(10)(11). Also, this technique was used for the genotyping of various Dehalococcoides groups in groundwater samples (17).…”
Section: Discussionmentioning
confidence: 99%